ТЕХНОЛОГИЯ ОБУЧЕНИЯ, ЕГО СУЩНОСТЬ. (Journal of Educational Sciences, 2016)
Педагогикалық орта оқушының тұлға ретінде жəне шығармашылық мүмкіндігін қалыптастыруда үлкен роль атқарады. Автор мақалада оқытудың технологиясы жəне оның мəні туралы баяндайды.The pedagogical environment has the big role in formation of pupils as persons and development of creative potential. The pedagogical environment for pupils can be divided into three groups: -Subject, - Information, - The psychological. New technologies of training can be accepted as the basic components of in detail psychological environment.